Organizational readiness to implement bundled interventions to increase HIV linkage and retention in care and treatment: results from the Black Women First (BWF) initiative - Angela Wangari Walter; Minu P. Mohan; Xiyuan Zhang; Melanie Rocco; Serena Rajabiun; Howard J. Cabral; Clara A. Chen; Esther Jennings; Julianne N. Dugas; Talitha Dantas; Judith C. Scott; Alicia Downes; et al. (BMC, 2024)
Abstract Background Evidence-based and evidence-informed interventions designed to address gaps in the HIV care continuum have the potential to improve HIV care and treatment. However, inadequate organizational readiness can derail intervention uptake, prevent the integration of interventions, and contribute to suboptimal HIV treatment outcomes. This study sought to understand organizational readiness to implement bundled interventions for Black women with HIV and inform facilitators and barriers to implementation. Methods We conducted a mixed methods readiness assessment across 12 sites participating in the Black Women First (BWF) initiative to gauge preparedness to implement bundled interventions. Readiness was assessed using the organizational readiness for implementing change (ORIC) scale, and two open-ended questions examined facilitators and barriers. Associations between participant and organizational level factors were evaluated using linear models with clustering by site at baseline, 6- and 12-months. Pre-implementation interviews were conducted with staff virtually and transcripts were managed in NVivo. Directed content analysis was used to explore implementation barriers and facilitators. Findings Sites demonstrated high levels of organizational readiness at baseline; overall organizational readiness for implementing change (ORIC) (mean 56.4, median 59, interquartile range [IQR] 5) and subscales of the ORIC change efficacy (mean 32.4, median 35, IQR 4), change commitment (mean 24, median 25, IQR 1), which is consistent with willingness and capability to implement bundled interventions for Black women with HIV. Organizational readiness remained high at 6- and 12-month follow-up periods. Staff role was significantly associated with organizational readiness (p = 0.007), change efficacy (p = 0.006), and change commitment (p = 0.020) at 6 months. Qualitative analysis indicated strategic planning and assessment (e.g., team coordination and the development of workflows to support implementation); organizational change through network weaving across silos within the organization, and communications systems that engage external partners, as well as resources available for hiring and training, supported readiness. Collaborative leadership and organizational buy-in, staff motivation, and partnerships facilitated implementation processes. Conclusions Organizations in the BWF initiative have high levels of organizational readiness reflecting willingness and capability to implement bundled interventions for Black women with HIV. Future research should examine the relationship between readiness and clinical outcomes.